Famílias monoparentais e feminização da pobreza no Brasil: estudo à luz da capabilities approach como plataforma de cidadania e proteção social - Oliveira, Pollyanna Souza (2021)
In the present study, the position of the Brazilian State in relation to female one parent families is examined. One starts from the hypothesis that such family arrangements - formed by a woman without a spouse and her minor children - have characteristics that expose them to vulnerability, due to the fact that it is exclusively assigned to women heads of household the role of provider, maintaining the typical survival strategies of nuclear family impaired, which relies on the spouse’s complementary financial resource. It is in this context that the concept of feminization of poverty, defined by the International Poverty Center (IPC), of the United Nations Development Program (UNDP), breaks out, from the increase of the difference in poverty levels between women and men or between households headed by women and those headed by couples or men. To compensate for this vulnerability, the State must provide minimum conditions for these women and their families to develop, namely in the light of the Capabilities Approach, which was thought by Amartya Sen and later expanded by Martha Nussbaum. In Brazil, notwithstanding the constitutional provision of the family entity formed by any of the spouses and their children, there is no sufficient legal regulation in the infraconstitutional area, with the exception of the temporary and exceptional regulation on emergency assistance [Law No. 13.982, of April 2, 2020, and its infralegal regulation], referring to the public health emergency imposed by the COVID-19 pandemic. Although demographic data reveal that the number of families headed by women is higher than those headed by men, there are no public policies specifically aimed at these family arrangements, as in other countries. In this master’s work, the theoretical axes of the expressions “one parent family” and “feminization of poverty” are addressed in counterpoint with the theoretical focus on capabilities and functionings, in the perspective of expanding the protective legal-political shield of the social State for these families, through public policies and specific actions.